2021
DOI: 10.3390/su13158661
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tax Incentives on Foreign Direct Investment: Evidence from Africa

Abstract: African countries have faced competition and several challenges to attract foreign direct investment given the role that FDIs play in the development process. Several efforts made have been futile because of numerous factors that play against the business environment for foreign investments. Our paper analyses the influence of tax incentives on foreign direct investment in African economies based on data from 2000–2018. We utilized panel data on forty (40) African countries and an econometric model of four pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
2
14
0
1
Order By: Relevance
“…Moreover, Zulaecha & Murtanto (2019) noted that firms controlled by multilateral and bilateral corporation significantly contributes to sustainable performance in Indonesia. Appiah-Kubi et al (2021) examined the relationship between tax incentives and the inflow of foreign direct investment in 40 African countries for the period of 2000-2018. Employing a robust random effect model the study found that foreign direct investment responds positively to lower corporate tax.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, Zulaecha & Murtanto (2019) noted that firms controlled by multilateral and bilateral corporation significantly contributes to sustainable performance in Indonesia. Appiah-Kubi et al (2021) examined the relationship between tax incentives and the inflow of foreign direct investment in 40 African countries for the period of 2000-2018. Employing a robust random effect model the study found that foreign direct investment responds positively to lower corporate tax.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though taxes have implications for government revenue, tax policy and its administration are a key part of country's private sector development strategy (Mawejje & Sebudde, 2019). Most empirical literature on the effect of tax on the private sector focuses on the relationship between tax incentives and FDI (Appiah-Kubi et al, 2021;Hsu et al, 2019;Mosquera Valderrama, 2020). A study by Klemm & Parys (2012) found that a decrease of 10% in corporate tax is associated with an increase in FDI between 0.33 and 4.5% of GDP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors [5], using corporate tax rate, withholding tax, tax holiday and tax concessions as proxies of tax incentives and Random Effect econometric model as a tool of analysis, the study analysed a panel data covering the period 2000-2018 from forty African economies. It was found that lower corporate tax (β=-0.784; t=-0.69; p=0.011) significantly affect FDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors [5] investigated the implication of taxation in FDI inflows in Pakistan. The study used Time Series data covering the period from 1985 to 2020 obtained from the World Development Indicator and the Economic Survey of Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%